2016
DOI: 10.1021/acs.iecr.5b04448
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Closed-Cell Rubber Foams Based on Natural Rubber/Carbon Black by One-Step Foam Processing

Abstract: A novel one-step compression molding was proposed and successfully employed for preparation of closed-cell foams based on natural rubber (NR)/carbon black (CB) composite. The uniqueness of this new method was that both the foam density and expansion ratio became independent of the CB content. The rheometrical findings indicated that the increase in the CB content from 0 to 20 phr yielded a 0.91 and 3.51 N m increase in the initial and the final torque, respectively. The SEM results demonstrated that the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 41 publications
(58 reference statements)
6
63
0
Order By: Relevance
“…The elongation at break of NRF/UG3 and NRF/CG3 were similar to that of unfilled NRF. Generally, the elongation at break of NRF composites decreased with increasing filler content due to the rigidity of fillers . However, in our case the addition of graphene particles does not impair the elongation at break of NRF nanocomposites, meaning that it can retain the elastic behavior of NRF product with high tensile strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elongation at break of NRF/UG3 and NRF/CG3 were similar to that of unfilled NRF. Generally, the elongation at break of NRF composites decreased with increasing filler content due to the rigidity of fillers . However, in our case the addition of graphene particles does not impair the elongation at break of NRF nanocomposites, meaning that it can retain the elastic behavior of NRF product with high tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…Some fillers (e.g., calcium carbonate , kenaf powder , and rice husk powder ) can significantly improve tensile strength and compressive stress of NRF only at high filler loading. Nevertheless, some fillers such as carbon black and NRF/organoclay nanocomposites can provide high impact on the properties of NRF. The intrinsic filler factors that effect on the final properties of NRF composites include filler geometry, size and size distribution, content, compatibility, filler‐polymer interaction and the functional group of filler.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these excellent properties, they have been used in many applications, including thermal and sound insulators, packaging, electromagnetic shielding materials, structural components and medical devices45. In recent years, elastic foams have been successful made from styrene butadiene rubber (SBR)6, poly(ethylene vinyl acetate) (EVA)7, poly(ethylene propylene diene) (EPDM)8, natural rubber (NR)9, polyurethane (PU)10 and polychloroprene rubber (CR)11. The literature review revealed that the rubber foams were mainly studied from two aspects: (a) their morphology, microstructure and resultant properties; (b) Physical and mechanical properties such as density, hardness, rebound resilience, compression set, tensile strength, tear strength and elongation at break.…”
mentioning
confidence: 99%
“…3 Since these materials are not vulcanized so they can be recycle and re-shape via a re-melting process similar a thermoplastic materials. [5][6][7] Carbon nanotubes (CNTs) are known as the ideal reinforcing fillers to produce high-performance nanocomposites with excellent mechanical, thermal, and electrical properties 8,9 compared with other fillers such as glass fiber, talc, calcium carbonate, carbon black, and carbon nanofiber. [5][6][7] Carbon nanotubes (CNTs) are known as the ideal reinforcing fillers to produce high-performance nanocomposites with excellent mechanical, thermal, and electrical properties 8,9 compared with other fillers such as glass fiber, talc, calcium carbonate, carbon black, and carbon nanofiber.…”
Section: Introductionmentioning
confidence: 99%